Gap Analysis of Accounting Curricula in Algerian Universities: Compliance with International Education Standards (IES) and Reform Imperatives - Dafri, Rima; Torchi, Meriem; Merabet, Hanane (Journal of Excellence for Economics and Management Research, 2026)
This study aims to identify and analyze the critical gaps between Algerian accounting education and the global benchmarks set by the International Education Standards (IES). Conducting a systematic gap analysis of university programs from Bachelor’s to Master’s levels, we identify critical misalignments in four dimensions: (1) pedagogical-experiential disconnect; (2) technological fragmentation; (3) superficial ethics integration; and (4) assessment misalignment. Findings reveal ceremonial compliance driven by faculty capability gaps and stakeholder decoupling. The importance of this research lies in its contribution to the modernization of accounting education in Algeria and similar emerging economies, which is crucial for fostering financial transparency, attracting investment, and building a profession capable of navigating complex global challenges. We propose transformative alignment via hybrid practice studios (practitioner co-teaching), digital immersion threads (blockchain/AI integration), and competency-based e-portfolios. This research provides an evidence-based framework for accounting education reform, emphasizing technological judgment and ethical acculturation as pillars of professional readiness.